Development of a device for cleansing cow udder teats and testing it under industrial conditions - Paliy, Andriy; Aliiev , Elchyn; Paliy , Anatoliy; Ishchenko , Katerina; Shkromada , Oksana; Musiienko , Yurii; Plyuta, Larysa; Chekan , Oleksandr; Dubin , Ruslan; Mohutova , Valentyna (Eastern-European Journal of Enterprise Technologies, 2021)
Preparing cows for milking is one of the most important operations. Not only the speed of milk production but also the quality of milk depends on the level of the work performed. One of the most effective ways to mechanize the preparation of cows for milking implies the development of a special mechanical brush that cleans and stimulates the teat skin. As a result, there is no need to use additional foam detergents and napkins to cleanse and disinfect teats. A device has been designed for cleansing teats with two rotating brushes. Theoretical studies of the interaction of cleansing elements of the device for mechanical removal of pollutants from the udder teats in the course of milking operation were carried out. Assuming constancy of the modulus of elasticity, shape and roughness of teats, linear and angular velocities of brushes, nap stiffness, and homogeneity of physical and mechanical properties of contaminants on the teat, dependence of force Fe of the mechanical device on length l of the cleansing element and its speed ω was established. Under the condition that force Fe of the mechanical device is smaller than force Fp which causes pain but greater than the force retaining pollutants (adhesion), values of the main design and technological parameters of the developed device were determined: l=8 mm, ω=106 rpm. As a result of production tests, it was found that when using the developed device, the daily milk yield of the experimental group of cows exceeded that of the control group by an average of 1.1 times which has made it possible to obtain a supplement of 132.5 kg of milk. Along with this, there was a 0.19 % increase in milk fat content in the experimental group compared to the control group. The number of microorganisms decreased 2.2 times and the number of contaminant particles decreased 4.6 times